2001
DOI: 10.1128/aem.67.4.1587-1593.2001
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Properties of Saccharomyces cerevisiae from Which Hexokinase II Has Been Deleted

Abstract: Hexokinase II is an enzyme central to glucose metabolism and glucose repression in the yeast Saccharomyces cerevisiae. Deletion of HXK2, the gene which encodes hexokinase II, dramatically changed the physiology of S. cerevisiae. The hxk2-null mutant strain displayed fully oxidative growth at high glucose concentrations in early exponential batch cultures, resulting in an initial absence of fermentative products such as ethanol, a postponed and shortened diauxic shift, and higher biomass yields. Several intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 47 publications
(41 reference statements)
3
55
1
Order By: Relevance
“…Figures 2A, 2C). This is caused by the much lower ethanol production during the predominantly oxidative growth on glucose and sucrose by the hxk2 deletion strain, whereas the wild-type strain converts glucose mainly to ethanol (see also Diderich et al, 2001). In the first 22 h, the RQ of the hxk2 deletion strain was close to 1, which is characteristic Figure 3.…”
Section: Glucose Repression Through Hxk2 Revisitedmentioning
confidence: 69%
See 1 more Smart Citation
“…Figures 2A, 2C). This is caused by the much lower ethanol production during the predominantly oxidative growth on glucose and sucrose by the hxk2 deletion strain, whereas the wild-type strain converts glucose mainly to ethanol (see also Diderich et al, 2001). In the first 22 h, the RQ of the hxk2 deletion strain was close to 1, which is characteristic Figure 3.…”
Section: Glucose Repression Through Hxk2 Revisitedmentioning
confidence: 69%
“…Accordingly, the hxk2 deletion strain displayed an increased flux through the TCA cycle and oxidative phosphorylation in the presence of excess glucose. The flux through glycolysis and the fluxes to ethanol and glycerol were decreased, resulting in almost exclusively oxidative growth and thus diminished ethanol production (Diderich et al, 2001). As a consequence, the growth yield of the hxk2 deletion strain during aerobic growth on glucose is much higher than that of its parent strain, since fermentation of glucose to ethanol yields only two ATPs per glucose consumed, whereas complete oxidation of glucose to carbon dioxide and water yields roughly 20 ATPs.…”
Section: Introductionmentioning
confidence: 98%
“…The process is blocked in a strain lacking glucose transport genes, and decreased in an hxk2⌬ strain in which fermentation is slowed (11). Furthermore, 2-deoxy glucose, which cannot enter glycolysis, does not substitute for glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in the literature show that the respiration of cells that accumulate F16bP to different degrees changes proportionally. It has been shown that the rate of oxygen consumption of the ⌬hxk2 mutant, lacking isoform 2 of hexokinase, which has lower levels of F16bP, is not inhibited by high glucose concentrations (25,47). A strain overexpressing phosphofructokinase has lower JO 2 values (48).…”
Section: Discussionmentioning
confidence: 99%